PENDAMPINGAN TRANSFER TEKNOLOGI FERMENTASI PADA PENGELOLAAN LIMBAH INDUSTRI PENGOLAHAN UDANG MENJADI PUPUK ORGANIK CAIR - Dikpride Despa; Dewi Sartika; Mardiana Mardiana (Jurnal Abdi Insani, 2026)
Shrimp farmers in Pekon Tanjung Jati Kabupaten Pesisir Barat face obstacles in processing shrimp pond waste. This waste has unknowingly become an environmental problem (pollution). To overcome this problem, the Community Service Team offers a solution to process waste into liquid organic fertilizer (POC) and environmentally friendly, cheap solid fertilizer. The technologies to be disseminated are: a) Anti-Microbial Technology, b) Simple fermentation technology, c) Technology for processing waste into solid fertilizer and liquid fertilizer (POC). The objectives of this Community Service are 1) transfer of simple fermentation technology; 2) solve partner waste problems by minimizing waste into products with sales value, 3) increase partner income with a new product, namely POC. The achievement methods used are a) lectures and discussions on simple fermentation technology, b) transfer of waste processing technology, c) mentoring in POC processing. Community Service Evaluation is carried out by testing the understanding and mastery of technology, both hard skills and soft skills, the concept of fermentation technology and natural antimicrobials and POC processing techniques at the beginning and at the end of the Community Service. The expected results of the Community Service are: increasing the understanding of 1) Fermentation technology and natural anti-microbials among partners by around 80-100%; 2) POC processing technology by 85%; (3) creating new products with sales value (80%). This entire series of activities also pays attention to Occupational Safety and Health and the Environment (K3L) aspects, by ensuring that the process is safe for partners and does not cause negative impacts on the surrounding environment.